The Description Of The Management Of Kurnia Computer Course And Training Institutions In The Pancung Soal District Pesisir Selatan Regency - Dalvino Yuliandoni; Alim Harun Pamungkas (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This research is motivated by several advantages possessed by the Kurnia Computer course and training institution such as gaining the trust to carry out job learning activities and entrepreneurship skills learning activities, having two programs that have been nationally accredited, having instructors who have national competence, training activities centered on community training and provide complete learning facilities. This research has a type of descriptive research. The population in this study amounted to 15 respondents, the sample used was 5 respondents who were used as respondents. This study has a description of the management of the Kurnia Computer course and training institution in Pancung Problem District, South Coast District. The information processing step used in data collection is using a questionnaire, the tool used is a questionnaire while the formula uses a percentage formula. The results of this study if the data on the management of the Kurnia Computer course and training institution in Pancung Problem District, Pesisir Selatan Regency is classified as very good. With good management by managers who have an influence on the implementation of Kurnia Computer training in Pancung Problem District, Pesisir Selatan Regency.